Fast Mapping Rapidly Integrates Information into Existing Memory Networks - Coutanche, Marc N. (J Exp Psychol Gen, 2014)
Successful learning involves integrating new material into existing memory networks. A learning procedure known as fast mapping (FM), thought to simulate the word-learning environment of children, has recently been linked to distinct neuroanatomical substrates in adults. This idea has suggested the (never-before tested) hypothesis that FM may promote rapid incorporation into cortical memory networks. We test this hypothesis here in two experiments. In our first experiment, we introduced fifty participants to sixteen unfamiliar animals and names through FM or explicit encoding (EE), and tested subjects on the training day, and again after sleep. Learning through EE produced strong declarative memories, without immediate lexical competition, as expected from slow-consolidation models. Learning through FM, however, led to almost immediate lexical competition, which continued to the next day. Additionally, the learned words began to prime related concepts on the day following FM (but not EE) training. In a second experiment, we replicated the lexical integration results, and determined that presenting an already-known item during learning was crucial for rapid integration through FM. The findings presented here indicate that learned items can be integrated into cortical memory networks at an accelerated rate through fast mapping. The retrieval of a known related concept, in order to infer the target of the FM question, is critical for this effect.